Laporan Kasus : Dekompresi Mikrovaskular pada Spasme Hemifasial (Neurologi Manado, 2020)
Hemifacial spasm (HFS) is a movement disorder of the seventh cranial nerve which is characterised by either brief or persistent intermittent twitching of the muscle innervated by the facial nerve. Although HFS is a benign disease, it can lead to increasing embarassment dan social withdrawl. There are several treatment for HFS, such as pharmacotherapy, botulinum toxin therapy, and microvascular decompression (MVD). MVD has been established as a first-line surgical treatment for patient with HFS and has been reported to provide relief from spasm in over 90% of cases. In this case, Female 47 years old, presenting with persistent intermittent twitching of his left facial muscle which getting worse for several years. Brain MRI showed compression of N.VII sinistra with left Anterior Inferior Cerebellar artery. Patient got consulted to neurosurgeon for DMV treatment, after she didn’t show any improvement with pharmacotherapy. After surgical, patient showed improvement in symptoms, follow up after 3 months is needed for evaluating prognosis of the patient.